Table of Content - - (Journal of Educational and Psychological Sciences, 2025)
Table of Content: • Suitability of U.S. School Accreditation Standards for Saudi Secondary Public Schools: Principals’ Perspectives Ms. Sarah Hamed Zerfeel Alotaibi • Sincerity as an Islamic Spiritual Competence: A Critical Analytical Study of the Dimensions of Sincerity Mr. Mustafa Mohamed Abdelmohiman, Mr. Osama Abdullah Al Saied ,Mr. Abdullah Hussein Salem, Dr. Wael Ahmed Abdalla Sabra • The Effect of Inquiry-Based Learning on Developing Scientific Research Skills and Motivation in Science among Preparatory Stage Students in Public Schools – Northern District Ms. Safa Ahmad Khaled Mareed Omari, Co-Prof. Fawaz Muhmad Abed Aqel • Standardization of the Childhood Autism Rating Scale (CARS2) on a Sample of Autistic Children in The Palestinian Interior (48) Ms. Raja’a Ebraheem Yasin Nassar • Learning Motivation and Its Relationship with Academic Achievement Among Female Students of the College of Education at the University of Hail Ms. Malkah Murdi Almutawea, Ms. Bashayr Nawaf Alshammari, Ms. Abrar Eid Alsuhaifi • Future anxiety and its relationship to self-efficacy among high school female students in Hail Ms. Fydaa Ghazi Al-Rashidi • Male international students’ experiences with their professors at a higher education institution in Saudi Arabia: A qualitative study Asst-Prof. Saud Ghassan Albeshir